(untitled) (Konferensiyalar | Conferences, 2024)
This work investigates the significant effects on education of having access to digital resources, technology, and online learning environments. Modern technology, which offers educators and students fresh resources and learning opportunities, is a major factor in reshaping the educational landscape. This article looks at how incorporating technology into education has improved student engagement, changed the way that traditional teaching methods are taught, and made high-quality education more accessible. It also explores the issues of equity, the digital divide, and the necessity of effective pedagogical strategies, among other challenges and opportunities related to digital learning. This article highlights how technology can transform education and establish more productive and inclusive learning environments by examining recent studies and industry trends.